Metabolism control by the circadian clock and vice versa - Eckel-Mahan, Kristin (2009)
Circadian rhythms govern a wide variety of physiological and metabolic functions in most organisms. At the heart of these regulatory pathways in mammals is the clock machinery, a remarkably coordinated transcription-translation system that relies on dynamic changes in chromatin states. Recent findings indicate that regulation also goes the other way, as specific elements of the clock can sense changes in the cellular metabolism. Understanding in full detail the intimate links between cellular metabolism and the circadian clock machinery will provide not only crucial insights into system physiology but also new avenues toward pharmacological intervention of metabolic disorders.